PENGARUH MODAL INTELEKTUAL DAN INDEKS PENGUNGKAPAN MODAL INTELEKTUAL TERHADAP NILAI PERUSAHAAN - Pambudi, Nindya Mawarni; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research has been conducted on manufacturing companies which are listed in Indonesia Stock Exchange(IDX) in 2011-2015 periods. The purpose of this research is to find out the influence of intellectual capital andindex of intellectual capital disclosure to the value of manufacturing companies which are listed in Indonesia StockExchange (IDX). The data is the secondary data in the form of annual report in each manufacturing companywhich is listed in Indonesia Stock Exchange (IDX) in 2011-2015 periods. The sample has been collected by usingpurposive sampling method and has been met the criteria of sample selection. The samples are 60 companies. Theintellectual capital has been measured by using Value Added Intellectual Capital (VAICTM) method. The indexof intellectual capital disclosure in this research has been measured by using 58 items disclosure index, and thefirm value has been measured by using Tobinâs Q ratio. The data analysis technique has been carried out by usingmultiple linear regressions analysis and the statistic hypothesis of F and t test. The result of this research statesthat intellectual capital gives positive influence to the firm value and index of intellectual capital disclosure givespositive influence to the firm value.Keywords: intellectual capital, index of intellectual capital disclosure, firm value